Iridium-Catalyzed Transfer Hydrogenation for Construction of Quinolines from 2-Aminobenzyl Alcohols with Enones in Water - Luo, Nanhua; Shui, Hongling; Zhong, Yuhong; Huang, Jiuzhong; Luo, Renshi (Synthesis, 2021)
Herein, we describe a method for the synthesis of functionalized quinolines from 2-aminobenzyl alcohols with α,β-unsaturated ketones. This method exhibits tolerance to various functional groups and high efficiency, is environmentally benign, and can be performed on a gram scale. Control experiments suggest that this transformation is accomplished by iridium complex catalyzed transfer hydrogenation, which is then followed by Friedländer cyclization. The results display that alkali is essential for the high selectivities of this catalytic system.
Keywords: iridium catalysis; transfer hydrogenation; quinolines; alcohols; enones